2009
DOI: 10.1080/02699930802044651
|View full text |Cite
|
Sign up to set email alerts
|

Understanding anhedonia in schizophrenia through lexical analysis of natural speech

Abstract: Anhedonia is a negative prognostic indicator in schizophrenia. However, the underlying nature of this emotional deficit is unclear. Laboratory studies examining patients' emotional reactions under controlled circumstances have failed to find evidence for a diminished hedonic response, instead finding that patients' reactions to laboratory stimuli are characterised by high levels of negative emotion. The present study employed lexical analysis of natural speech in 52 patients and 49 nonpatient controls while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 64 publications
1
40
1
Order By: Relevance
“…The finding that word use categories explained over a quarter of the variance in overall symptoms is particularly compelling. Although a previous study found that individuals with schizophrenia high in anhedonia produced more negative emotion words in pleasant conditions than those low in anhedonia or healthy controls (Cohen et al, 2009), the current study is the first to use lexical analysis to demonstrate how word use is related to the full range of schizophrenia symptoms. Our observation that word use categories significantly predicted symptoms cannot be accounted for by shared method variance, as word use and symptoms were assessed using separate interviews.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that word use categories explained over a quarter of the variance in overall symptoms is particularly compelling. Although a previous study found that individuals with schizophrenia high in anhedonia produced more negative emotion words in pleasant conditions than those low in anhedonia or healthy controls (Cohen et al, 2009), the current study is the first to use lexical analysis to demonstrate how word use is related to the full range of schizophrenia symptoms. Our observation that word use categories significantly predicted symptoms cannot be accounted for by shared method variance, as word use and symptoms were assessed using separate interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Higher percentages indicate more frequent word use (see Table 1 for raw data and examples of categories/ subcategories). LIWC has demonstrated good validity for measuring verbal emotional expression (Kahn et al, 2007), and has been used previously to assess word use in schizophrenia (Buck et al, In Press;Cohen et al, 2009;Hong et al, 2013;Junghaenel et al, 2008;St-Hilaire et al, 2008).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we primarily made use of the default LIWC 2007 dictionary, we also used one word category from the LIWC 2001 dictionary ): "optimism." The LIWC software has been used previously in samples of individuals with schizophrenia-spectrum disorders (Cohen et al, 2009;Junghaenel et al, 2008;Lee et al, 2007;St. Hilaire et al, 2008) and has demonstrated validity for measuring verbal emotional expression (Kahn et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, lexical analysis been used to examine correlates of characteristics within schizophrenia samples, such as emotions, symptoms, and functioning. For example, Cohen et al (2009) linked anhedonia and negative emotion words in schizophrenia, and Minor et al (2015) linked negative emotion and social words to symptoms, metacognition, and general functioning in this population. Buck et al (2015) furthered work with anhedonia by investigating anticipatory and consummatory pleasure and lexical qualities, with findings indicating past-words and first-person plural pronouns (e.g., we, our) are associated with both types of pleasure in this population.…”
Section: Introductionmentioning
confidence: 99%